What Ever Happened to Global Architecture? Rethinking the Shift from Global to Glocal Culture in Architecture and Cities - Güleç, Gülşah (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The argument of this paper is that there has been a shift from global to glocal culture in architecture and cities. Cultural studies focusing on the processes of globalization and localization suggest that glocalization has emerged as a new strategy for understanding the reality of cities, with glocal cities having both global and local characteristics. The glocal is not the opposite but the alternative mode of the global. The paper argues that globalization and localization, respectively, lead to cities and architecture being defined in terms of homogeneity and heterogeneity, but glocalization paves the way for them to be redefined through hybridity. In addition, glocal cities are seen as transnational places unlike cities characterized by their global or local cultures. The paper thus presents a new perspective for seeing and understanding the current state of cities and architecture, which cannot be reduced to either a global or a local structure. According to this perspective, architectural designs are discussed as glocal products, because they are built in a local place, but their design ideas and images circulate in a global context. They are defined by local globalities, revealing the fact that it is not the global or the local, but the glocal that is the new emerging reality of cities.